Inteligencia Computacional Aplicada a la Evaluación de Calidad de Servicio - Salcedo Parra, Octavio José; Manta Caro, Héctor Cristyan; Aparicio Pico, Lilia Edith (Ingeniería, 2006)
The quality of service QoS evaluation specifically in the packet routing satisfies requirements of performance and maximizes the resources utilization of the network by means of paths selection based on the resources that are needed. More in the investigations about the quality of service support in the routing are focused in the one-domain routing, BGP, the standart for the inter-domain routing does not provide mechanism to evaluate the quality the service and taking in consideration that the quality of service experienced by the users, it is influenced by all domains through the end-to-end path, it is necessary the development of schemes of inter-domain routing that evaluate efficiently the quality of service. The proposed research is focused in the computational intelligence application in a prototypeof interdomain routing based in policies. We present a fuzzy logic approach to evaluate the quality of service, in this way selectpaths depending multiple heterogeneous criteria.